Marine Residence, Gasparillo Island, Trinidad - Rice, Ben (Bonanza Smith Bros. and Co.,[Trinidad and Tobago], 2011)
This postcard shows some vacation houses on the hills of one of the Minor Bocas Islands off the north western coast of Trinidad, Gasparillo Island (Little Gasparee or Centipede Island).
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Vacation homes--Trinidad and Tobago; Dwellings--Trinidad and Tobago